Early clearance of Chikungunya virus in children is associated with a strong innate immune response - Diane, Simarmata; Ng, David Chun Ern; Yiu-Wing, Kam; Lee, Bernett; Magdline Sia, Henry Sum; Her, Zhisheng; Chow, Angela; Yee-Sin, Leo; Jane, Cardosa; Perera, David; Ooi, Mong How; Ng, Lisa F.P. (Nature Publishing Group, 2016)
Chikungunya fever (CHIKF) is a global infectious disease which can affect a wide range of age groups. The pathological and immunological response upon Chikungunya virus (CHIKV) infection have been reported over the last few years. However, the clinical profile and immune response upon CHIKV infection in children remain largely unknown. In this study, we analyzed the clinical and immunological response, focusing on the cytokine/chemokine profile in a CHIKV-infected pediatric cohort from Sarawak, Malaysia. Unique immune mediators triggered upon CHIKV infection were identified through meta-analysis of the immune signatures between this pediatric group and cohorts from previous outbreaks. The data generated from this study revealed that a broad spectrum of cytokines/chemokines is up-regulated in a sub-group of virus-infected children stratified according to their viremic status during hospitalization. Furthermore, different immune mediator profiles (the levels of pro-inflammatory cytokines, chemokines and growth and other factors) were observed between children and adults. This study gives an important insight to understand the immune response of CHIKV infection in children and would aid in the development of better prognostics and clinical management for children.